Lysostaphin-Induced, Osmotically Fragile Staphylococcus aureus Cells - Huber, T. W. (1970)
Staphylococcus aureus FDA 209P cells when suspended in 24% (w/v) NaCl were rendered osmotically fragile by exposure to lysostaphin for time intervals ranging from 2 to 60 min. Such cells were analyzed chemically and serologically for evidence of residual cell wall material, were plated in hypertonic sucrose medium to determine revertibility to normal, and were subjected to manometric studies to determine metabolic capabilities. Most of the cells (95%) which were exposed to lysostaphin (0.5 or 1.0 unit/ml) for 2 min, although osmotically fragile, retained their cell wall hexosamine and were capable of reverting to osmotically normal cells when plated in hypertonic medium. Cells exposed to lysostaphin for 5 and 10 min also retained much of their cell wall hexosamine, but lost their ability to revert to normal staphylococci. Cells exposed to lysostaphin for 2 to 10 min continued to react with staphylococcus anti-k antiserum. Complete removal of cell wall hexosamine was attained only after exposure to lysostaphin for 20 min or more; these cells failed to react with k antiserum. Lysostaphin-induced L-type colonies were extremely rare in our experiments, even if incubation times and media were optimal for their detection. Lysostaphin-induced staphylococcal protoplasts were as active metabolically in manometric studies as were untreated staphylococci.